Investigation of Potato (Solanum tuberosum L.) Salt Tolerance and Callus Induction in vitro - Pepó, Pál; Tóth, Szilárd (Acta Agraria Debreceniensis, 2005)
Potato production plays an important role in Hungary and the other countries of Europe. Consumption of potato products has increased to a large extent during the past several years. We can satisfy market demands with high quality and virus-free varieties.Results of potato production depend on tolerance/resistance to abiotic stresses. In many cases, increased concentration of NaCl causes yield loss. Selection of salt tolerant varieties proved to be a difficult problem. Nowadays, the salt tolerance of potato varieties can be determined by cell/tissue/ protoplast techniques. Somaclonal variation provides a great potential for selection of lines resistant to salt stress. In vitro shoots and callus, derived plantlets selected for salt tolerance/resistance provide material for micropropagation.In vitro shoot development of potato (Solanum tuberosum L. cv. Kuroda) was investigated under salt stress (40 mM, 80 mM, 120 mM NaCl) conditions. Shoot heights of plantlets cultured under salt conditions were lower than the control through the investigation. However, the shoot development of plantlets originated from in vitro meristems was almost at the same level as the control under 40 mM NaCl concentration.There was no significant difference in the in vitro biomass production between control and treatment with 40 mM NaCl concentration. We measured a significant decrease in dry-matter mass under 120 mM NaCl concentration. There is a need for more investigation of different genotypes and for a conclusion as to whether in vitro tolerance could occur under in vivo circumstances in plants originated from somaclones as well.Under in vitro conditions, we investigated shoot and leaf callus initiation using different culture media with different 2,4-D concentrations. Under dark conditions, callus induction of shoot/leaf decreased as the 2,4-D concentrations increased.In light conditions, there was a little callus induction, while callus initiation from the shoot from 5 μM to 12 μM 2,4-D concentration showed a significant increase